2019
DOI: 10.1088/1755-1315/403/1/012109
|View full text |Cite
|
Sign up to set email alerts
|

Sheep productivity when probiotic feed additive “Amilocin” introduced into the diets

Abstract: The paper presents the results of a study on the effect of probiotic feed additive “Amilotsin” on the productivity of pregnant ewes and castrate rams. The ewes who received the optimal level of Probiotic feed additive (PFA) “Amilotsin” in the diet throughout the entire experiment were significantly superior in their live weight to their analogues. Animals of the second group at the end of the experiment had a live weight higher by 3.4% than in the first and by 2.4% compared to the third group. The highest aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As a dietary supplement, probiotics also showed positive effects on carcass weight and meat quality [ 46 , 47 ]. Such effects on meat quality includes improvement of product quality and shelf life [ 3 ], upgrading the sensory qualities [ 12 , 13 ], and improving color and tenderness [ 5 , 12 ] and healthy fatty acid profiles [ 48 , 49 ]. The beneficial effects of probiotics supplements on carcass weight and meat quality are exhibited in Figure 3 .…”
Section: Effects Of Probiotics On Meat Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…As a dietary supplement, probiotics also showed positive effects on carcass weight and meat quality [ 46 , 47 ]. Such effects on meat quality includes improvement of product quality and shelf life [ 3 ], upgrading the sensory qualities [ 12 , 13 ], and improving color and tenderness [ 5 , 12 ] and healthy fatty acid profiles [ 48 , 49 ]. The beneficial effects of probiotics supplements on carcass weight and meat quality are exhibited in Figure 3 .…”
Section: Effects Of Probiotics On Meat Qualitymentioning
confidence: 99%
“…Liu et al [ 12 ] reported that probiotic supplements increased the density of fibers in muscle, which causes softness and tenderness of meat. Several other studies reported that probiotic supplements improved meat color, flavor, and tenderness; thus, panelists preferred probiotic supplemented meat to meat without probiotic supplements [ 48 , 52 ]. In addition, dietary probiotic supplements might also alter the composition of volatile compounds, which is linked to the quality attributes of meat [ 5 , 12 ].…”
Section: Effects Of Probiotics On Meat Qualitymentioning
confidence: 99%
“…Diets used in agricultural enterprises to feed animals most often do not cover nutrient requirements. Therefore, the need arises for its enrichment with various feed additives, incorporating biologically active substances and having positive effect on health and reproductive functions of animals [20][21][22]. In this regard, agribusiness secondary raw materials are of great interest, namely, starch-treacle production (gluten, germ, pulp, sirup and others) [23].…”
Section: Introductionmentioning
confidence: 99%